A descriptive analysis of anglicism used in Ecuadorian mazines - Ramírez Camba, Patricia Clarivel (2012)
This study analyzes Anglicisms present in the current written language in Ecuadorian magazines, in the way they are influencing Spanish communication. Anglicisms are English words used as idiomatic borrowings in other language. The investigation consists on a descriptive and linguistic analysis of the lexical terms in order to gather information to identify and analyze the Anglicisms presently used in Ecuadorian magazines. This study is performed in Guayaquil-Ecuador, with six Ecuadorian magazines, which correspond to the variables, classified in three groups: two cultural, two scholarly and two general interest magazines. The methods used to execute this study are the Qualitative and Quantitative Methods, where the Anglicisms collected are classified in tables in order to establish the variable containing the highest number of Anglicisms, and to determine the mostly used ones. The results show that the most common Anglicisms used in the selected magazines correspond to the branches of computer science and technology, and it also demonstrates that the insertion of these words is mainly caused by the lack of an equivalent in Spanish.